Research ethics and integrity for social scientists : beyond regulatory compliance - Israel, Mark (Los Angeles : SAGE, 2016)
Ethics is becoming an increasingly prominent issue for all researchers across the western world. This comprehensive and accessible guide introduces students to the field and encourages knowledge of research ethics in practice.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 13, 2016).
Keywords: elektronické knihy; electronic books; Social sciences -- Research -- Moral and ethical aspects